Autoimmunity in psoriatic arthritis: pathophysiological and clinical aspects - DİRESKENELİ, RAFİ HANER (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2022)
Psoriatic arthritis (PsA) is an underdiagnosed entity with a broad impact on the quality of life. Although the pathogenesis is largely unknown, autoimmune footprints of the inflammation in PsA have increasingly been recognized. Most of the genetic variation predisposing to PsA is mapped to the class I major histocompatibility complex (MHC) region and shared by a variety of autoimmune diseases. Polymorphisms in the genes IL12B, IL23R, IL13, TNIP1, TRAF3IP2, TYK2, and many others explain the non-HLA genetic risk with little known functional consequences. Entheseal and synovial cellular infiltrate with oligoclonal CD8(+) T cells and occasional germinal centers, loss of regulatory T cell function, and specific autoantibodies such as anti-PsA peptide, anti-LL-37, and anti-ADAMTSL5 are the immunopathological findings suggestive of autoimmunity. 'hese were supported by clinical observations of autoimmune multimorbidity and treatment response to calcineurin/mTOR and co-stimulation inhibition.
Keywords: Autoantibody; autoimmunity; genetic; psoriasis; psoriatic arthritis; HUMAN-LEUKOCYTE ANTIGEN; SYSTEMIC-LUPUS-ERYTHEMATOSUS; QUALITY-OF-LIFE; HLA CLASS-I; GENE POLYMORPHISMS; SUSCEPTIBILITY LOCUS; PEMPHIGUS-VULGARIS; ASSOCIATION; DISEASE; RISK